A compact wideband circularly polarized antenna with two pairs of driven patch arrays. Issue 11 (2nd September 2020) - Liu, Wen‐Wen; Cao, Zhen‐Hua; Wang, Zhi
Abstract: In this article, a new wideband circularly polarized (CP) antenna is presented. The antenna is composed of a circular‐loop feeding structure which provides sequential phase (SP), four primary‐parasitic crown patches and four secondary‐parasitic crown patches. The circular‐loop SP structure is used to feed the two pairs of crown patches by a capacitively coupled way. The presented antenna features a wide 10‐dB impedance bandwidth (IBW) of 23% (6 GHz, 5.31‐6.69 GHz), and a wide 3‐dB axial ratio bandwidth (ARBW) of 11.1% (5.875 GHz, 5.55‐6.2 GHz). The proposed antenna features compact structure and broad 3 dB‐ARBW, which could include the WLAN (5.725‐5.85 GHz), ITS (5.8 GHz), and WIFI (5.85‐5.925 GHz) band.